ZOSTAĆ CZY WRACAĆ? METAFORYCZNIE O REEMIGRACJI POLAKÓW PO BREXICIE - Fel, Stanisław; Kozak, Jarosław; Wódka, Marek (Polityka i Społeczeństwo, 2020)
Poles represent one of the largest groups of economic immigrants to the UK. As a result of Brexit, many of them have redefined their migration scenarios, which has affected the economy and some areas of social and cultural life in the UK. This paper presents the results of our original quantitative study conducted in the autumn of 2019 on a sample of 620 Polish respondents living in three locations in England – London, Oxford, and Swindon. The study addresses the question Do Polish migrants intend to return to Poland, and if they do, when? and examines to what extent this decision is influenced by the length of their stay in England, by their financial situation, by their knowledge of English, by their ability to assimilate culturally, by how much they miss their family, by homesickness, and by their craving for Polish culture. The article follows the typology of attitudes adopted by Poles towards Brexit, as identified by Agnieszka Trąbka and Paulina Pustułka.